If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8x = 10 + -15x Solving 12 + -8x = 10 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 12 + -8x + 15x = 10 + -15x + 15x Combine like terms: -8x + 15x = 7x 12 + 7x = 10 + -15x + 15x Combine like terms: -15x + 15x = 0 12 + 7x = 10 + 0 12 + 7x = 10 Add '-12' to each side of the equation. 12 + -12 + 7x = 10 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 10 + -12 7x = 10 + -12 Combine like terms: 10 + -12 = -2 7x = -2 Divide each side by '7'. x = -0.2857142857 Simplifying x = -0.2857142857
| 40=12m-20 | | 2x^3+5x^2+6x-8=0 | | (-8+8i)-(5+4i)= | | m-3.1=7 | | 9x-7y=10fory | | 70*n=60 | | 2x-143=711 | | 0=3.4x-4.9x^2 | | 11=2q-40 | | 64*n=24 | | 5-3r=19 | | 4q+12=18 | | 4-8x=3(1-2x)-5x | | (6x+8)(8x-6)= | | 4=5x-31 | | 4x-5=13x-15 | | -1/2(x-4)-1/5(x-5)=x+9 | | n+(n+1)=111 | | g(x)=-3x^2+0.06x+4 | | (x-4)/(x-3)-(x-1)/(3-x) | | x/4+17=9 | | (5)/(t-1)+3/t | | 23.4-x=0 | | 2x+5-9=3x-15 | | -3=18-x | | 2n+5=4(n+2)-a | | p-6p=-4 | | 4y-9=13 | | 2y+6x=-14 | | n+17=35 | | n+25=30 | | x^3+14x^2+52x+21=0 |